Science and the Tatshenshini Controversy - Bell, Anne (UnderCurrents: Journal of Critical Environmental Studies, 1996)
One of the more celebrated conservation success stories in recent Canadian tory was the protection of the British Columbian portion of the Tatshenshini watershed. Plans to mine a copper deposit at Windy Craggy Mountain, near one of the river's tributaries, were brought to an abrupt halt after the provincial government decided to set the area aside as a Class A Provincial Park in June, 1993. The decision was the result of intensive lobbying efforts on the part of groups and individuals who feared the impacts of mining on wildlife and on a place unmarred by roads, dams and industrial development. [...]